2018
DOI: 10.1016/j.biombioe.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the minimum fluidization velocity of particles of sugarcane bagasse

Abstract: A B S T R A C TThis study refers to an experimental analysis of the fluid-dynamics of particles of sugarcane bagasse in a fluidization column with an internal diameter of 190 mm, which determined the minimum fluidization velocity of the particles with different characteristic diameters (0 < dp < 9.5 mm), using air as fluidization means. The results have shown that the minimum fluidization velocity has a tendency to increase as the diameter of the particle increases. However, in a certain range of diameter (0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Tannous and Lorenço [10] reported that their correlation for determining apparent fluidization velocity was valid for Reynolds number values between 1.4 and 14, as observed in Eq. (9). Mixtures of pinus bark and sand and eucalyptus bark and sand of this experiment were outside the range established by the authors but are nevertheless shown in Table 7.…”
Section: Comparison With Prediction Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…Tannous and Lorenço [10] reported that their correlation for determining apparent fluidization velocity was valid for Reynolds number values between 1.4 and 14, as observed in Eq. (9). Mixtures of pinus bark and sand and eucalyptus bark and sand of this experiment were outside the range established by the authors but are nevertheless shown in Table 7.…”
Section: Comparison With Prediction Methodsmentioning
confidence: 59%
“…Biomass characteristics such as density, size and sphericity directly affect the fluidization. Pérez et al [9] carried out a study on the fluid dynamics of a scale fluidized bed with 190 mm of internal diameter and 2500 mm in height, using air as a fluid phase and sugarcane bagasse as biomass. The authors investigated the effects of particle diameter, density and shape on the fluid dynamics behavior and compared the experimental results of the minimum fluidization velocity with different correlations presented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…12,56 As shown in Figure 3, it was possible to determine the complete fluidization point from the pressure drop versus superficial gas velocity profiles by identifying the intersection between the rising pressure drop line and the flattened pressure drop line. 12,56 It is clear that silica sand fluidized at relatively lower superficial velocities and had the least pressure drop ΔP/H, which could be attributed to these particles being smaller in diameters and having high sphericity. 4 Due to interparticle cohesive forces, the pressure drop first increased with superficial gas velocity, and then after the minimum fluidization point, it dropped sharply before becoming constant (i.e., it did not change on any further increase in the superficial gas velocity).…”
Section: Artificial Neural Network Modelmentioning
confidence: 99%
“…Accurate knowledge of the minimum fluidization velocity is fundamental in understanding the hydrodynamic behavior of binary systems in the fluidized bed [15]. The general method of pressure drop vs. superficial gas velocity is employed to determine the minimum fluidization velocity in this section.…”
Section: Fluidization Behaviors Of Binary Systemsmentioning
confidence: 99%